2012
DOI: 10.1128/aac.00447-12
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Small-Molecule Therapy Prevents Uropathogenic Escherichia coli Catheter-Associated Urinary Tract Infections in Mice

Abstract: ABSTRACTCatheter-associated urinary tract infections (CAUTIs) constitute the majority of nosocomial urinary tract infections (UTIs) and pose significant clinical challenges. These infections are polymicrobial in nature and are often associated with multidrug-resistant pathogens, including uropathogenicEscherichia coli(UPEC). Urinary catheterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 65 publications
1
92
0
Order By: Relevance
“…In addition, mannoside compounds acted synergistically with TMP-SMZ to further reduce the level of CFU recovered from catheters and bladders 6 hours after infection (38). Unfortunately, these compounds, despite their efficacy in preclinical models, remain to be tested in clinical trials and are not currently available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mannoside compounds acted synergistically with TMP-SMZ to further reduce the level of CFU recovered from catheters and bladders 6 hours after infection (38). Unfortunately, these compounds, despite their efficacy in preclinical models, remain to be tested in clinical trials and are not currently available.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with mannoside compounds, which block the binding of UPEC to the bladder surface and prevent colonization, effectively limited implant and bladder colonization in a model of UPEC CAUTI when delivered intraperitoneally 30 minutes prior to catheterization (38). In addition, mannoside compounds acted synergistically with TMP-SMZ to further reduce the level of CFU recovered from catheters and bladders 6 hours after infection (38).…”
Section: Discussionmentioning
confidence: 99%
“…When tested in a mouse model, the mannosides were able to prevent UTI when given prophylactically or to treat an established chronic urinary tract infection (275). These molecules have been demonstrated to prevent and treat UPEC CAUTI in a mouse model (276). Furthermore, synergistic action was noted between mannosides and trimethoprim-sulfamethoxazole, suggesting the utility of adjuvant approaches in this setting (276).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…These molecules have been demonstrated to prevent and treat UPEC CAUTI in a mouse model (276). Furthermore, synergistic action was noted between mannosides and trimethoprim-sulfamethoxazole, suggesting the utility of adjuvant approaches in this setting (276). Prophylactic administration of a mannoside molecule, compound ZFH-04269, was recently demonstrated to significantly reduce bacterial colonization of the bladder and to prevent acute UTI caused by an epidemic multidrug-resistant UPEC ST131 clone.…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…It is well documented that type 1 pili are important for the invasion and persistence of the UPEC in the urinary bladder after its colonization. Type 1 pili colonization is enhanced by adhesin FimH (Hannan et al, 2012) encoded by fimH gene which recognizes certain α1β3 integrins (Guiton et al, 2012;Eto et al, 2007). It was also confirmed that FimH is important in pathogenesis and that the pathogenicity of a UPEC strain depends greatly on the ability of FimH to switch between conformations and this is also dependent on the different alleles that can be expressed by this gene, affecting FimH conformation …”
Section: Discussionmentioning
confidence: 57%